Spousal age difference and associated predictors of intimate partner violence in Nigeria - Ayo Stephen Adebowale (BMC, 2018)
Abstract Background The growth in Intimate Partner Violence (IPV) cases among couples in Nigeria has been significant in recent years. Victims, which are often females, face numerous health challenges, including early death. I examined the linkages between spousal age differences and IPV in Nigeria. Method The couples recode data section of the 2013 Nigeria Demographic Health and Survey was used (n = 6765). Intimate partner violence was measured using 13-item questions. Data were analyzed using the logistic regression model (α = .05). Results The mean spousal age difference was 8.20 ± 5.0 years. About 23.5, 18.0, 13.5 and 4.7% of couples surveyed had experienced some form of IPV, emotional, physical and sexual violence respectively. Also, IPV prevalence was 27.0, 23.7, 22.0 and 18.7% among couples with age differences of 0-4, 5-9, 10-14 and ≥15 years respectively; this pattern was exhibited across all domains of IPV. Among women who experienced physical violence, 20.5% had only bruises, 8.0% had at least one case of eye injuries, sprains and/or dislocations, and 3.7% had either one or more cases of wounds, broken bones or broken teeth. The identified predictors of IPV were: family size, ethnicity, household wealth, education, number of marital unions and husband drinks alcohol. The unadjusted likelihood of IPV was 1.60 (C.I = 1.30-1.98, p < 0.001) and 1.35 (C.I = 1.10-1.64, p < 0.01) higher in households where the spousal age difference was 0-4 and 5-9 years respectively, than the likelihoods among those with a spousal age difference ≥ 15 years, but the strength of the association weakens when other variables were included in the model. Conclusion The level of IPV was generally high in Nigeria, but it reduced with increasing spousal age difference. This study underscores the need for men to reach a certain level of maturity before marriage, as this is likely to reduce the level of IPV in Nigeria.